Frontispiece: Synthesis of Dihydroindoloisoquinolines through Copper‐Catalyzed Cross‐Dehydrogenative Coupling of Tetrahydroisoquinolines and Nitroalkanes. Issue 71 (18th December 2018) - Martín‐García, Iris; Alonso, Francisco
Abstract : The cross‐dehydrogenative coupling (CDC) of tetrahydroisoquinolines and nitroalkanes has been extensively reported to produce β‐nitroamines, typically under copper catalysis. A very different outcome has been observed when using copper nanoparticles on titania (CuNPs/TiO2 ) as the catalyst, giving rise to dihydroindoloisoquinolines. Three carbon−hydrogen bonds are converted into two carbon−carbon bonds in one step with a catalytic system that is simple, works under aerobic and solvent‐free conditions, requires relatively low excess of the nitroalkane in the absence of ligands and oxidant chemicals, shows good functional group compatibility and better performance than a broad array of commercial copper catalysts. This represents a straightforward access into the family of biologically active 5, 6‐dihydroindolo[2, 1‐ a ]isoquinolines. For more information, see the Communication by F. Alonso and I. Martín‐García on page 18857 ff.